The Other Voice in the Room: Restorative Justice Facilitators' Constructions of Justice. (March 2014) - Paul, Gregory D.; Dunlop, Julia A.
Abstract Restorative justice represents an approach to managing conflict initiated by a wrongdoing that focuses on restoring the participants materially, psychologically, and relationally. Restorative interventions usually involve facilitators who act as experts in helping the parties manage their conflict restoratively. They also help participants understand how restorative justice differs from traditional justice and what restorative justice looks like. However, we lack an understanding of how facilitators conceptualize justice in the first place. Drawing on interviews with facilitators, this study identifies facilitators' justice constructions during victim‐offender conferences. Together, these constructions constitute a multidimensional, multilayered model of justice in victim‐offender conferences.